‘The learning never ends’ Investigating teachers’ experiences of moving from English for General Purposes to English for Academic Purposes in the UK context; What are the main challenges associated with beginning to teach EAP, and how can these challenges be overcome? - Campion, Gemma (2012)
English for General Purposes (EGP) and English for Academic Purposes (EAP) are seen as two distinct branches of English Language Teaching, and much is made in the literature of the differences between the two fields. Despite this, experience of EGP is officially recognised as appropriate experience for teaching EAP, but no stipulations are made about how EGP teachers should be trained or supported when making such a large transition. Whilst there are a number of different EAP-specific teacher training courses on offer, at present the status of such courses remains somewhat unclear. This study attempts to investigate teachers’ experiences of making the transfer from EGP to EAP, particularly focusing on the challenges they experienced and how teachers feel those challenges can best be overcome. The study also seeks to gain teachers’ thoughts about the role and value of EAP-specific teacher training. Semi-structured interviews were conducted with six EAP teachers who have varying degrees of experience. The results reveal that teachers feel the greatest differences between teaching EGP and EAP concern the development of the specialised knowledge needed to teach EAP, whilst relative confidence is experienced in terms of teachers’ existing teaching skills. The results also reveal the range of activities that teachers feel help them to overcome the challenges, and recommendations are made for how institutions can do more to facilitate this type of development. EAP-specific teacher training courses are deemed potentially valuable in a number of ways, but teachers do not feel that such training would be most usefully used as a pre-requisite of entry to the profession. The results suggest that what is perhaps needed is a change in emphasis which would see pre-service EAP-specific training as an initial step in a much larger, on-going framework of EAP teacher development.